The Transcription Factor Function of Parkin: Breaking the Dogma - Alves da Costa, Cristine; Duplan, Eric; Rouland, Lila; Checler, Frédéric (Frontiers in Neuroscience, 2019)
PRKN (PARK2) is a key gene involved in both familial and sporadic Parkinson’s disease that encodes parkin (PK). Since its discovery by the end of nineties, both functional and more recently, structural studies led to a sticky tag of PK as an E3-ligase only. It is generally considered that this function conditions the cellular load of a subset of cytosolic proteins prone to proteasomal degradation and that a loss of E3-ligase function triggers an accumulation of potentially toxic substrates and, consequently, a neuronal loss. Further, PK molecular interplay with PTEN-induced kinase 1 (PINK1), a serine threonine kinase also involved in recessive cases of Parkinson’s disease, is considered to underlie mitophagy process. Thus, since mitochondrial homeostasis significantly governs cell health, there is a huge interest of the scientific community centered on PK function. In 2009 we have demonstrated that PK could also act as a transcription factor and induces neuroprotection via the down-regulation of the pro-apoptotic and tumor suppressor factor, p53. Importantly, the DNA binding properties of PK and its nuclear localization suggested an important role in the control of several genes. The duality of PK subcellular localization and of its associated ubiquitin-ligase and transcription factor functions, suggests that PK could behave as a key molecular modulator of various physiological cellular signaling pathways that could be disrupted in pathological contexts. Here we update the current knowledge on PK direct and indirect transcription factor-mediated control of gene expression